Capital Adequacy, Credit Risk, and Efficiency in Islamic Bank Profitability - Hani, Fathi; Saputri, Ika Puji; Randyantini, Vely (Involvement International Journal of Business, 2025)
Islamic commercial banks have gained prominence in Indonesia’s financial system, yet their profitability still lags behind conventional banks. Understanding the financial determinants that influence the profitability of these institutions is critical for improving their competitiveness and ensuring sustainable growth. This study investigates the effects of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operating Costs to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on bank profitability, measured by Return on Assets (ROA). This research adopted a quantitative approach using secondary data from the annual financial statements of 12 Islamic commercial banks registered with the Financial Services Authority (OJK) of Indonesia, covering the years 2019 to 2023. Multiple linear regression analysis was applied after conducting descriptive statistics and classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The regression model was used to examine the relationship between the four independent variables (CAR, NPF, BOPO, FDR) and ROA. The findings show that CAR and FDR have a significant positive effect on ROA, indicating that strong capital adequacy and efficient liquidity management improve profitability. In contrast, NPF and BOPO negatively affect ROA, demonstrating that high credit risk and operational inefficiency diminish bank performance. The regression model explains 72.3% of the variance in ROA, confirming the robustness and relevance of the selected variables in determining profitability. The results are consistent with agency and liquidity preference theories and highlight the distinctive challenges faced by Islamic banks, such as compliance-related costs and limitations in accessing conventional financial instruments. Operational efficiency, credit quality, and liquidity management emerge as critical strategic areas.